Comparison of neurally adjusted ventilatory assist and synchronized intermittent mandatory ventilation in preterm infants after patent ductus arteriosus ligation: a retrospective study - Hui-Zi Lin; Yun-Feng Lin; Yi-Rong Zheng (BMC, 2024)
Abstract Objective This study aimed to compare the efficacy of neurally adjusted ventilatory assist (NAVA) to synchronized intermittent mandatory ventilation (SIMV) in preterm infants requiring mechanical ventilation after patent ductus arteriosus (PDA) ligation. Methods A retrospective analysis was conducted on intubated preterm infants who underwent PDA ligation at our hospital from July 2021 to January 2023. Infants were divided into NAVA or SIMV groups based on the ventilation mode after surgery. Results Fifty preterm infants were included. During treatment, peak inspiratory pressure (PIP) and mean airway pressure (MAP) were lower with NAVA compared to SIMV (PIP: 19.1 ± 2.9 vs. 22.4 ± 3.6 cmH2O, P < 0.001; MAP: 9.1 ± 1.8 vs. 10.9 ± 2.7 cmH2O, P = 0.002). PaO2 and PaO2/FiO2 were higher with NAVA (PaO2: 94.0 ± 11.7 vs. 84.8 ± 15.8 mmHg, P = 0.031; PaO2/FiO2: 267 [220-322] vs. 232 [186-290] mmHg, P = 0.025). Less sedation was required with NAVA (midazolam: 1.5 ± 0.5 vs. 1.1 ± 0.3 μg/kg/min, P < 0.001). Conclusion Compared to SIMV, early use of NAVA post PDA ligation in preterm infants was associated with decreased PIP and MAP. Early NAVA was also associated with reduced sedation needs and improved oxygenation. However, further studies are warranted to quantify the benefits of NAVA ventilation.